SYNTHESIS AND QUALITATIVE STRUCTURE ACTIVITY RELATIONSHIPS OF SOME 1,5-DIPHENYL 1,4-PENTADIEN-30NE AND CYCLICS ANALOGUES - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT: Some new compounds of series of 2,6-bis(4-hydroxy-3-methoxybenzylidene) cyclohexanone (A), 2,5-bis(4-hydroxy-3-methoxybenzylidene) cyclopentanone (B) and 1,5-bis(4-hydroxy-3-methoxypheny1)-1,4- pentadiene-3-one (C) analogues have been synthesized. These compounds have been identified and the physical properties have been characterized. Their antioxidative activity as anti lipid peroxidation (Lipidperoxictation = LPO), antiinflammatory as anticy clooxygenase (Cyclocxygenase =Cox, and anti-oedema and their antibacterial activity have been investigated. The synthesis were performed according to modified Rumpel, i.e., they were carried out by condenÂ¬sation of a corresponding aromatic aldehydes with a six or five ring membered ketone or acetone under acidic or alkaline condition. The purity of the synthesized compounds was determined based on their melting point and thin layer chromatographic (TLC) analyses. The elucidation of structure of all compounds has been confirmed using spectrometric techniques including infrared (IR) (KBr), nuclear magnetic resonance ('H-NMR) ( 8 , ppm, CDC1, or d6-DMSO, and mass spectrometer (MS) (El, m/z) techniques. The data analyses showed thatC compounds (C series) (olefins) were presentin the E-form (EntgeÂ¬gen form). The coupling constants of two protons attached to double bond of olefinic group are arround 16 Hz. Also the A and B series have the E-configuration. In Z isomer the benzene ring was not in the same plane with the planar plane that formed by the olefinic double bond, so the ortho hydrogen atom would interact with the oxygen atom of the carbonyl group, was resulted in the decrease of the resonance energy and therefore the Z-isomer was unfavourable. Anti-LPO activity was determined by the so-called thiobarbituric acid (TBA) test, using microsomes of rat liver as polyunsaturated fatty acids (PUFA) source. In the LPO process malon dialdehyde (MD A) was formed and reacts with thiobarbituric acid (TBA) to give a pink coloured chromogen. The chromogen was measured spectrophotometrically. Cox inhibition activity has determined using platelets of fresh human blood as Cox source, while arachidonic acid used as a substrate. The pink coloured chromogen formed was then measured spectrofluorometrically. Oedema inhibition activity was established by injecting a small amount of cairagenan to left hind paw of the rat. The extent of induced-oedemic was measured using phletismograph. The compounds to be tested were given orally. The anti-oedemia effect was determined by comparison with control. The antimicrobial activity of the compounds was established by measuring the inhibition zones in gelatine test. All compounds having hydroxy group in para position, were active as antioxidant, except 2,6-bis(4- hydroxy-3,5-dichlorobenzylidene)cyclohexanone (A 16) and l,5-bis(4-hydroxy-3,5-dichloro- phenyl)-1,4- pentadiene-3-one (C16). Removing one carbonyl and methylene groups of curcumin (leading to Cl) decreased anti- oxidant activity less than that of the curcumin. On the other hand the dimethoxy 2,6-bis(4-hydroxy-3,5- dimethoxybenzylidene)cyclohexanone(A15),2,5-bis(4-hydroxy-3,5-dimethoxybenzyl idene) cyclopentanone (B15) and 1,5-bis(4-hydroxy-3,5-dimethoxy phenyl)-1,4-pentadiene-3-one (C1 5) was more potent than either Cl and curcumin